Intergenerational Transmission of Inequality: Maternal Endowments, Investments, and Birth Outcomes - Sadegh S. M. Eshaghnia; James J. Heckman (Institute of Labor Economics (IZA), 2023)
Newborn health is an important component in the chain of intergenerational transmission of disadvantage. This paper contributes to the literature on the determinants of health at birth in two ways. First, we analyze the role of maternal endowments and investments (education and smoking in pregnancy) on the probability of having a baby who is small for gestational age (SGA). We estimate both the total impact of maternal endowments on birth outcomes, and we also decompose it into a direct, "biological" effect and a "choice" effect, mediated by maternal behaviors. Second, we estimate the causal effects of maternal education and smoking in pregnancy, and investigate whether women endowed with different traits have different returns. We find that maternal cognition affects birth outcomes primarily through maternal education, that personality traits mainly operate by changing maternal smoking, and that the physical fitness of the mother has a direct, "biological" effect on SGA. We find significant heterogeneity in the effects of education and smoking along the distribution of maternal physical traits, suggesting that women with less healthy physical constitutions should be the primary target of prenatal interventions.
Keywords: I12; I14; J24; 330; health production; intergenerational transmission; human capital